Influência dos hormônios sexuais masculinos sobre a reatividade vascular de artérias mesentéricas de terceira ordem: uma avaliação temporal - Rouver, Wender do Nascimento (2020)
Male sex hormones have been associated with a risk of cardiovascular disease, but this relationship is not fully understood. Studies that aim to elucidate the role of androgens on vascular reactivity have pointed out divergences, mainly regarding the part